Fibrillarin-GFP Facilitates the Identification of Meiotic Competent Oocytes - Wang, Ting; Na, Jie (Frontiers in Cell and Developmental Biology, 2021)
Nucleolus undergoes significant functional change and plays important roles during mammalian oocyte meiotic maturation. Fibrillarin (FBL) is the component of nucleolar small nuclear ribonucleoprotein (snRNP) particle and localizes to the dense fibrillar component (DFC) of the nucleolus. We found that FBL-GFP displays an uneven and cloudy localization in the nucleolus of non-surrounded nucleolus (NSN) oocytes, while it distributes evenly and to a few bright dots in the surrounded nucleolus (SN) oocytes. Accordingly, NSN oocytes showed active nascent RNA transcription, while the SN group was transcriptional quiescent. NSN geminal vesicles also contained more DNA damage marker H2AX foci. Based on different FBL-GFP patterns in live oocytes, the ones with superior meiotic maturation potential can be identified. Global transcriptome profiling revealed a significant difference in single SN and NSN oocytes. Thus, FBL-GFP can serve as a marker for nucleolus activity, which also correlates with transcription activity and the quality of oocytes.